2005
DOI: 10.1177/0091270005275368
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentrations of Everolimus Are Markedly Increased by Ketoconazole

Abstract: The authors sought to quantify the influence of the CYP3A and P-glycoprotein inhibitor ketoconazole on the pharmacokinetics of everolimus in healthy subjects. This was a 2-period, single-sequence, crossover study in 12 healthy subjects. In period 1, subjects received the reference treatment of a single 2-mg dose of everolimus. In period 2, they received the test treatment of ketoconazole 200 mg twice daily for a total of 8 days and a single dose of everolimus coadministered on the fourth day of ketoconazole th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 8 publications
5
52
1
1
Order By: Relevance
“…When everolimus was coadministred with ketoconazole, a potent cytochrom 3A4 inhibitor, in 12 healthy volonteers, a 15-fold AUC 0→Tlast increase has been observed, as compared to everolimus group alone. Also, a 1.9-fold prolongation of elimination half-life (30 ± 4 vs 56 ± 5 h) was shown [12]. Verapamil is described like an important inhibitor of P-gp and less important inhibitor of cytochrom 3A while ketoconazole is both a potent inhibitor of P-gp and cytochrom 3A.…”
Section: -Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When everolimus was coadministred with ketoconazole, a potent cytochrom 3A4 inhibitor, in 12 healthy volonteers, a 15-fold AUC 0→Tlast increase has been observed, as compared to everolimus group alone. Also, a 1.9-fold prolongation of elimination half-life (30 ± 4 vs 56 ± 5 h) was shown [12]. Verapamil is described like an important inhibitor of P-gp and less important inhibitor of cytochrom 3A while ketoconazole is both a potent inhibitor of P-gp and cytochrom 3A.…”
Section: -Discussionmentioning
confidence: 86%
“…The CYP 3A represent almost 30% of the cytochromes in the liver and 70% of the cytochromes in the small intestine [10]. Many studies have demonstrated that inhibitors of cytochromes 3A are leading to an increase of AUC of drug substrates with a prolongation of half time elimination [11,12]. P-gp is part of a large family of efflux transporters which is expressed in the gonads, kidneys, biliary system, intestinal epithelium, brain capillaries and lymphocytes.…”
Section: -Introductionmentioning
confidence: 99%
“…Orally administered sirolimus exhibits a substantial PK drug interaction with ketaconazole, resulting in increased whole blood exposure to sirolimus (Zimmerman, 2004). Oral structural analogues of sirolimus (tacrolimus and everolimus) are also CYP3A4 substrates and exhibit strong drug interactions with ketoconazole (Kovarik et al, 2005(Kovarik et al, , 2006El-Dahshan et al, 2006). This drug interaction study was conducted in healthy adults to assess the PK profile of a single i.v.…”
mentioning
confidence: 99%
“…Interestingly, steady-state serum levels reached by this compound in in vivo treated patients [40,41,42] are much higher than those demonstrated to be able to induce γ-globin gene expression in erythroid precursor cells from β-thalassaemia patients. Therefore, everolimus might be considered for pre-clinical trials to determine whether it has an effect on HbF production.…”
Section: Discussionmentioning
confidence: 99%